Karakter Anak di Desa Wagirlor, Ngebel, Ponorogo dalam Dunia Game dan Media Sosial - Tegar Prasetyo Nugroho (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The advancement of information and communication technology, particularly the internet, has significantly influenced the lives of people in both urban and rural areas. One of its impacts can be observed in the character development of children in Wagirlor Village, Ngebel Subdistrict, Ponorogo Regency, who actively use social media and online games. This study aims to explore how the use of digital media shapes and affects children’s character. The research employed a qualitative descriptive method through field observations, interviews with children and parents, as well as a literature review. The findings indicate that social media and online games have positive impacts, such as enhancing creativity, cooperation, competitive spirit, and providing opportunities in the creative economy. On the other hand, negative effects were also identified, including addiction, reduced face-to-face social interactions, declining interest in learning, and low digital literacy. The study concludes that digital media has two contrasting sides, and therefore, guidance from parents, teachers, and the community is crucial to ensure that children can use technology wisely, maintain balance, and uphold moral values as well as local culture.